Analysis of Inhibiting Factors Achievement of Basketball STKIP Pasundan Cimahi - Kurnia, Dedi; Septiana, Rama Adha; Hidayatulloh, Selmy (STKIP Paasundan Press, 2023)
This study aims to measure how big the inhibiting factor for the achievement of the basketball Unit at STKIP Pasundan Cimahi. The method used in this research is descriptive quantitative and uses a survey research design. In this study, researchers used a google form questionnaire instrument. In this study, the population involved was 17 people and the researcher took a sample of 17 people using a total sampling technique. From the results of this study, the inhibiting factors for the achievement of UKM basketball STKIP Pasundan Cimahi are (1) Lack of facilities and infrastructure, (2) Management is not organized by the campus, (3) The lack of funding received by UKM, (4) athletes (SDM). With a percentage of 88%, this study concludes that the inhibiting factors for the achievement of UKM basketball STKIP Pasundan Cimahi are the lack of facilities and infrastructure, less organized management by the campus, the lack of funding received by UKM, and few human resources so that it can have a big impact on achievement. UKM basketball STKIP Pasundan Cimahi.